iTAG an optimized IMiD-induced degron for targeted protein degradation in human and murine cells - Habib Bouguenina; Stephanos Nicolaou; Yann-Vaï Le Bihan; Elizabeth A. Bowling; Cheyenne Calderon; John J. Caldwell; Brinley Harrington; Angela Hayes; P. Craig McAndrew; Costas Mitsopoulos; Fernando Jr. Sialana; Andrea Scarpino; et al. (iScience, 2023)
Summary: To address the limitation associated with degron based systems, we have developed iTAG, a synthetic tag based on IMiDs/CELMoDs mechanism of action that improves and addresses the limitations of both PROTAC and previous IMiDs/CeLMoDs based tags. Using structural and sequence analysis, we systematically explored native and chimeric degron containing domains (DCDs) and evaluated their ability to induce degradation. We identified the optimal chimeric iTAG(DCD23 60aa) that elicits robust degradation of targets across cell types and subcellular localizations without exhibiting the well documented “hook effect” of PROTAC-based systems. We showed that iTAG can also induce target degradation by murine CRBN and enabled the exploration of natural neo-substrates that can be degraded by murine CRBN. Hence, the iTAG system constitutes a versatile tool to degrade targets across the human and murine proteome.